Effect of dried distillers grains on quality of dough and bread - Cunjian Tu; Qiang Wang; Xinhong Liang; Ning Li; Ruixiang Zhao; Lingxia Jiao; Junjian Ran; Junchao Huang (Journal of Functional Foods)
Dried distillers grains are rich in dietary fiber and protein. Dried distillers grains was added to wheat flour to improve the nutrition and sensory quality of wheat flour staple food. The effects of Dried distillers grains on the thermomechanical properties and rheological properties of wheat flour dough were studied. After the addition of Dried distillers grains, the water absorption and protein weakening degree of the dough increased significantly. Simultaneously, the stability time and formation time decreased significantly. These changes indicate that Dried distillers grains has a substantial influence on the network structure of protein in wheat flour dough and on the gluten strength of the dough. Interestingly, the increase in the elastic modulus (G′) and viscous modulus (G′′) indicates enhanced stability in the dough structure, resulting in reduced fluidity and viscosity. Texture analysis revealed that Dried distillers grains could significantly reduce bread hardness within the 2–8 % range, while also increasing the specific volume of the bread. The sensory score reached its highest point with an 8 % substitution of Dried distillers grains. These results demonstrate that the addition of 2–8 % Dried distillers grains improves the quality of the bread.